Combined resection of lung cancer and thoracic aortic wall with simultaneous thoracic aortic endografting: a case report - Hiroaki Komatsu; Nao Furukawa; Hirotaka Kinoshita; Atsutaka Aratame; Toshio Baba; Kazunori Okabe (Surgical Case Reports, 2024)
Abstract Background Combined resection of lung cancer and the thoracic aortic wall with thoracic aortic endografting has been reported. However, whether the resection and endografting should be performed simultaneously or in two steps remains controversial. Case presentation A 68-year-old man was referred to our hospital because of left chest pain. Chest contrast-enhanced computed tomography revealed a huge tumor of the left lower lung lobe, and invasion to the aortic wall was suspected. Bronchoscopic examination was performed, revealing squamous cell carcinoma with a programmed death ligand 1 expression level of 90%. The clinical stage was T4N0M0 stage 3A. After neoadjuvant chemotherapy and radiotherapy, we performed one-stage surgery with the patient in the right lateral decubitus position and the left inguinal region exposed for femoral vessel isolation. Posterolateral thoracotomy was performed with making a latissimus dorsi muscle flap. The pulmonary artery, vein, and left lower bronchus were cut with a stapler. After hilar isolation, we evaluated the involvement of the descending aorta and marked the area of the involved aortic wall by a surgical clip. Using the left femoral artery approach, a GORE TAG conformable thoracic stent graft was delivered to the descending aorta. After thoracic aortic endografting, the involved aortic wall was resected and the left lower lobe of the lung and resected aortic wall were resected en bloc. The adventitial defect was covered by the latissimus dorsi muscle flap. The operating time was 474 min, and the blood loss volume was 330 mL. The postoperative pathological diagnosis was adenocarcinoma with an epidermal growth factor receptor mutation of exon 19 deletion. The residual viable tumor was 7 mm in diameter and close to the resected aortic wall. The patient’s postoperative course was uneventful. Five days after surgery, chest contrast-enhanced computed tomography revealed no endoleak or stent migration. Three months after surgery, he was alive with neither recurrence nor stent graft-related complications. Conclusions One-stage surgery involving combined resection of lung cancer and the thoracic aortic wall with simultaneous thoracic aortic endografting in the right lateral decubitus position with the left inguinal region exposed is safe and acceptable.